2015
DOI: 10.1002/jcp.25188
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Inheritance of mRNA Facilitates Translational Activation of the Osteogenic-Lineage Commitment Factor Runx2 in Progeny of Osteoblastic Cells

Abstract: Epigenetic mechanisms mediate the acquisition of specialized cellular phenotypes during tissue development, maintenance and repair. When phenotype-committed cells transit through mitosis, chromosomal condensation counteracts epigenetic activation of gene expression. Subsequent post-mitotic re-activation of transcription depends on epigenetic DNA and histone modifications, as well as other architecturally bound proteins that ‘bookmark’ the genome. Osteogenic lineage commitment, differentiation and progenitor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Gene expression analyses were performed using semi‐quantitative PCR as described previously [Varela et al, ] as a reproducible method that permits direct visualization of amplified cDNAs. Quantitation of mRNA expression detected by PCR was subsequently validated with next generation RNA sequencing (RNA‐seq) data that were concurrently generated for SAOS, MG63 and U2OS cell lines using procedures we previously described [Dudakovic et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression analyses were performed using semi‐quantitative PCR as described previously [Varela et al, ] as a reproducible method that permits direct visualization of amplified cDNAs. Quantitation of mRNA expression detected by PCR was subsequently validated with next generation RNA sequencing (RNA‐seq) data that were concurrently generated for SAOS, MG63 and U2OS cell lines using procedures we previously described [Dudakovic et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Runx2 also known as core binding factor α1 (Cbfa1) is an important transcription factor involved in osteogenic differentiation of BMSCs. Its activation has been recognized as an initiation signal for the commitment of BMSCs to osteogenesis [47]. Actually, it induces osteogenesis both in vivo and in vitro by binding with the cis-element of the osteocalcin gene and initiates the transcription of some osteogenic genes [48].…”
Section: Transcription Factors Involved In Osteogenic Differentiationmentioning
confidence: 99%
“…These findings indicated that Runx2 plays an essential role in osteogenic differentiation and demonstrated the ability to use Runx2 gene transfer to enhance the differentiation of MSCs into osteocytes (Zhao et al, 2005). The post-mitotic symmetric segregation of Runx2 mRNA to progeny cells has been also found to support the maintenance of osteogenic lineage commitment and osteoblast phenotype (Varela et al, 2015). Homeobox protein Hox-B7 (HOXB7) over-expression affected the mRNA expression of the key transcription factor, Runx2, and promotes osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%